المحافظات غير المنتظمة في إقليم بين المركزية واللامركزية الإدارية - كاظم حسن الربيعي (Journal of Madenat Alelem University College, 2011)
By highlighting the legal governorates old and new shows that botn aaopted decentralized management, whether in law or in the Constitution, for the Act | No. 159 of 1969, which ran until 2008 according to the reasons for it been necessary legislation law, the Department supports the principles of administrative decentralization to achieve the aspirations and expectations of its citizens, for this nominated boards through democratic elections, state-sponsored at the time, and supervised by the Minister of the Interior is empowered by these councils in all provinces clear and definite authority to walk affairs and even more of them now have an independent budget and fixed income, but that these powers did not last long but affected by political circumstances and social conditions prevailing then exported Legislative Reform Act No. 35 of 1977, which said (that every society where there are one authority, one for each state its political one and that means there is the idea of the multiplicity of the legislative, executive and judicial branches of this has become necessary to reconsider the law of the provinces to remain a representative of the central authority in the country) this is disabled the provincial councils election and to put the appointment on the side of the election on the boards of the provinces and limited membership in the provincial councils of these appointees only, without elected not to mention the disruption of many of the powers and functions granted to the boards of the provinces and limit the validity of all However, the central authority from the Minister to the Governor, to the greatest staff in the far marshes and villages and districts in addition to the regulations and instructions that determine the freedom of the central persons in the ownership, mobility and travel, journalism and publishing and other. In the Constitution of the Republic of Iraq for the year 2005 is the time, which went first to the establishment of territories within six months from the date of issuance by request of one third of the members of the provincial council or a tenth of the voters in each province returned issued a Law of Governorates not organized into a Region No. 21 of 2008 for the purpose of organizing jurisdiction and powers in line with the shape of the new state-based federal system, federal and decentralized system as stated in the reasons for this law is not the whole truth, but because of faltering experience in the Kurdistan region and its readiness for independence from Iraq with the knowledge of an independent and an independent budget, army and police special tags and the limits of the disputed As stated in Article 140 of the Constitution do not know how it is permissible for lawmakers mention of the disputed border and tame them with the Iraqis they term a border with neighboring countries and not the boundary between the provinces of Iraq, which is subject to the Central Authority identified only .